(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Osteonecrosis is one of the most common musculoskeletal complications in sickle cell anaemia. Osteonecrosis of the femoral head (ONFH) is a prevalent and particularly debilitating alteration, with the frequency ranging from 9% to approximately 37%. Patients with ONFH suffer from the impact of subchondral bone collapse, producing pain and reduction in the functional capacity of the hip, school performance and health-related quality of life. Objectives: The study aimed to assess the prevalence and comorbidities of osteonecrosis of the femoral head in sickle cell disease among male and female patients of all ages in Saudi Arabia. Methods: This was a cross-sectional study, carried out from August 2023 to September 2024. By using the qualtrics calculator, our sample size was 384. Structured questionnaire was used as study tool. This tool developed after consulting relevant studies conducted in Saudi Arabia. Analysis of data was entered into the computer using the ‘Microsoft Office Excel Software’ program 2016 for windows. The data was transferred to the Statical Package for the Social Sciences (SPSS) software program. Results: As regard the prevalence of SCD symptoms among our study participants, most respondents, 93.5% out of 261 participants, reported experiencing symptoms of the disease with 38.9% experienced pelvic problems and 89.3% out of them were due to non-traumatic causes, indicating a high prevalence of symptomatic cases within the surveyed population. In term of associated comorbidities, 83.5% of participants reported hospitalization due to the disease, with a considerable proportion experiencing multiple hospitalizations per year. The prevalence of acute chest syndrome and pelvic problems among respondents was notable, with 51.7% and 39.8% respectively. As regard, relation between experiencing pelvic diseases and sociodemographic characteristics, we have found a statistically significant relation to age (p value=0.018), marital status (p value=0.0001), weight (p value=0.0001), and height (p value=0.0001). It also shows statistically insignificant relation to gender and region of residence. Conclusion: the study highlighted the high prevalence of symptomatic cases of sickle cell disease among patients in Saudi Arabia, with a significant proportion experiencing symptoms of osteonecrosis of the femoral head. The findings underscore the need for increased awareness and management of this debilitating condition, particularly in light of the associated complications and hospitalizations reported by the participants. Furthermore, the study revealed important sociodemographic factors that may influence the development of pelvic problems in patients with sickle cell disease.